Labour market programmes and geographical mobility: migration and commuting among programme participants and openly unemployed - Urban Lindgren; Olle Westerlund (Institute for Labour Market Policy Evaluation (IFAU), 2003)
We study migration and commuting among participants in labour market programmes and individuals in open unemployment. Post-programme mobility of participants in Employment Training, which is a supply-orientated program, is compared to the mobility of individuals participating in two demand-orientated programmes and the openly unemployed. The empirical results indicate higher geographical mobility among participants in Employment Training as compared to participants in Relief Work and the Work Experience Scheme. Individuals participating in Employment Training also have a higher probability of mobility than the openly unemployed. In this case, this is due to the relatively higher probability of commuting that predominates the relatively lower probability of migration. Hence, our results indicate that different labour market programmes are associated with different amounts of post-programme mobility. Moreover, using functional regional labour markets as the regional entity, we find interregional commuting to be relatively more important than migration as a means of geographical labour mobility.
Keywords: J61; 330; Geographical labour mobility; labour market programmes; migration; commuting